Modified LaMnO3 perovskite oxide catalyst as well as preparation method and application thereof

By modifying the LaMnO3 perovskite oxide catalyst, using acid etching and heat treatment to improve catalytic activity and stability, the equipment corrosion and chlorine pollution problems of toluene oxidation in the prior art were solved, and efficient and environmentally friendly benzoic acid preparation was achieved.

CN119771395APending Publication Date: 2025-04-08YANGZHOU UNIV

Patent Information

Application Number
CN202510116874.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art has problems such as serious equipment corrosion, large amount of chlorine-containing wastewater treatment and chlorine-containing products when producing benzoic acid, and lacks green and efficient liquid-phase oxidation methods for toluene.

Method used

LaMnO3 perovskite oxide catalyst was prepared by sol-gel method, and the catalyst was modified by acid etching and heat treatment to improve its specific surface area, channel size and pore volume, enhance catalytic activity and stability, and applied to toluene solvent-free oxidation to prepare benzoic acid.

Benefits of technology

A modified LaMnO3 perovskite oxide catalyst with high specific surface area, high catalytic activity, high selectivity and good recycling is achieved. The conversion of toluene and the selectivity of benzoic acid reach 24.8% and 82.7% respectively, avoiding the introduction of chlorine. The obtained benzoic acid is suitable for use in the medical and food fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771395A_ABST
    Figure CN119771395A_ABST
Patent Text Reader

Abstract

The invention discloses a modified LaMnO3 perovskite oxide catalyst as well as a preparation method and application thereof, and belongs to the field of catalyst modification. The preparation method of the modified LaMnO3 perovskite oxide catalyst comprises the following steps: (1) preparing the LaMnO3 perovskite oxide; and (2) carrying out acid etching treatment and heat treatment on the LaMnO3 perovskite oxide, and obtaining the LaMnO3 perovskite oxide after the acid etching treatment and the heat treatment are finished. According to the method, perovskite oxide is modified in an etching mode, the LaMnO3 perovskite oxide catalyst with high catalytic activity and high stability is synthesized by adding a heat treatment process, the LaMnO3 perovskite oxide catalyst is used in the process of preparing benzoic acid through methylbenzene solvent-free oxidation, no chlorine element is introduced, and the prepared high-quality benzoic acid can be widely applied to medical treatment and food. When the catalyst is used in a reaction for preparing benzoic acid through selective oxidation of toluene, the conversion rate of toluene can reach 24.8%, the selectivity of benzoic acid can reach 82.7%, and the catalyst has good activity and selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalyst modification, and specifically relates to a modified LaMnO3 perovskite oxide catalyst and a preparation method and application thereof. Background Art

[0002] Benzoic acid is an important chemical intermediate and can be used in the production of amides, esters, alcohols, etc. Benzoic acid and its sodium and potassium salts are often used as food preservatives, as flow diversion agents in crude oil extraction, and can also be used in the synthesis of polyesters, plasticizers, dyes, etc. At present, the industry mainly uses the chlorination hydrolysis process of toluene to produce benzoic acid. This process has disadvantages such as severe equipment corrosion, large amount of chlorine-containing wastewater treatment, and chlorine content in the product. Therefore, the industry and academia have been trying to develop green and efficient methods for the liquid phase oxidation of toluene. As a potential substitute for precious metals, perovskite oxide catalysts have been deeply studied in the oxidation of VOCs and water treatment due to their low cost, high stability, and high oxidation activity.

[0003] As a star material, perovskite oxides have always attracted much attention. Pathreeker et al. found that during the oxidation process of CaMnO3, the migration of calcium ions and the rearrangement of oxygen atoms lead to changes in the crystal structure, which may form Ca x The phenomenon of coexistence of multiple phases such as MnO3 and MnO2 (Journal of Electroanalytical Chemistry, 2020, Volume 874, Pages 114453-114458). The invention patent with publication number CN110026185A discloses a LaMnO3 perovskite supported on cordierite, which is modified by etching and applied to toluene degradation. The patent did not explore the effect of heat treatment on the catalytic activity and stability of the catalyst, and was not applied to the solvent-free selective oxidation of toluene to produce benzoic acid from the modified LaMnO3 perovskite. Summary of the invention

[0004] Objectives of the invention: The first objective of the present invention is to provide a modified LaMnO3 perovskite oxide catalyst having high specific surface area, high catalytic activity, high selectivity, relatively high density of oxygen vacancies, and excellent recyclability. The second objective of the present invention is to provide a method for preparing the above-mentioned modified LaMnO3 perovskite oxide catalyst. The third objective of the present invention is to provide an application of the above-mentioned modified LaMnO3 perovskite oxide catalyst.

[0005] Technical solution: The preparation method of the modified LaMnO3 perovskite oxide catalyst provided by the present invention comprises the following steps:

[0006] (1) Preparation of LaMnO3 perovskite oxide;

[0007] (2) The LaMnO3 perovskite oxide is subjected to acid etching and heat treatment to obtain a modified LaMnO3 perovskite oxide catalyst.

[0008] Further, in step (1), LaMnO3 perovskite oxide is prepared by a sol-gel method, the steps are:

[0009] (11) dissolving La(NO3)2·6H2O and Mn(NO3)2·4H2O in deionized water, stirring, adding citric acid as a chelating agent, and continuing to stir until completely dissolved to obtain a mixed solution;

[0010] (12) heating and stirring the mixed solution until the solution gradually becomes viscous and eventually forms a stable viscous gel;

[0011] (13) The viscous gel is dried, ground, and calcined to obtain LaMnO3 perovskite oxide.

[0012] Furthermore, in step (11), the molar ratio of La(NO3)2·6H2O to Mn(NO3)2·4H2O is 1:1-1.1, the dosage ratio of La(NO3)2·6H2O to solvent is: 0.015 mol:100-120 mL, the solvent is deionized water, and the molar ratio of citric acid to total metal ions is 1:1-1.1; in step (12), the process parameters of heating and stirring are: stirring in an oil bath at 80-85°C for more than 5 hours; in step (13), the process parameters of drying are: drying at 100-120°C for 12-20 hours; the process parameters of calcination are: calcining at 400-450°C for 2-2.5 hours, heating to 750-780°C and continuing calcining for 4-6 hours, and then naturally cooling to room temperature.

[0013] Further, in step (2), the process parameters of the acid etching treatment are: etching with a dilute nitric acid solution with a molar concentration of 0.5-1.0 mol / L for 200-280 min, preferably, the process parameters of the acid etching treatment are: etching with a 0.5 mol / L nitric acid solution for 210-230 min; after the acid etching process is completed, it also includes filtration, drying and grinding: the precipitate obtained by the acid etching treatment is repeatedly filtered with a circulating water vacuum pump until the filtrate is neutral, and the obtained filter cake is dried and ground; the process parameters of the heat treatment are: heat treatment at 300-700°C for 1-48h, preferably, the heat treatment parameters are: heat treatment at 400-700°C for 1-24h, more preferably: heat treatment at 500°C for 24h.

[0014] The present invention provides a modified LaMnO3 perovskite oxide catalyst prepared by the above preparation method.

[0015] Furthermore, the catalyst has a crystal size of 20-30 nm and a specific surface area of ​​60-70 m 2 / g, pore volume is 0.4-0.5cm 3 / g, with an average pore size of 30-40nm and a high concentration of oxygen vacancies. It has high activity and stability in the solvent-free oxidation process of toluene, and the conversion rate of toluene and the selectivity of benzoic acid can reach 24.8% and 82.7%, respectively.

[0016] The present invention provides the use of the modified LaMnO3 perovskite oxide catalyst in the selective oxidation of toluene to produce benzoic acid.

[0017] Furthermore, the application method is: using modified LaMnO3 perovskite oxide as a catalyst and oxygen as an oxidant to oxidize toluene under solvent-free conditions to produce benzoic acid.

[0018] Furthermore, the ratio of the modified LaMnO3 perovskite oxide to toluene is 0.10-0.50 g:10 mL, preferably 0.10-0.25 g:10 mL, and the oxidation conditions are: reaction temperature of 150-180°C, reaction time of 1-48h, oxygen pressure of 1-3MPa, and stirring speed of 200-1200rpm.

[0019] Principle of the invention: In the present invention, the sol-gel method is used to prepare perovskite oxide, which is conducive to the uniform mixing of raw materials at the molecular level in the solvent, and the preparation of perovskite oxide catalysts with uniform composition and structure, so that the active sites on the catalyst surface are more evenly distributed, thereby improving the catalytic efficiency and selectivity. Using citric acid as a chelating agent is conducive to stabilizing metal ions, controlling ion release and forming a porous structure through complexation, and realizing low-temperature self-combustion and ensuring product purity by virtue of combustion characteristics. The perovskite oxide is modified by acid etching to increase its active site density, and then heat treatment is used to improve stability. Etching can selectively remove a portion of the A-site lanthanum ions and significantly increase the specific surface area, pore size and pore volume of the catalyst. Continuing heat treatment improves the stability of the structure and activity of the catalyst. The prepared catalyst is applied to the reaction of toluene solvent-free oxidation to produce benzoic acid.

[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The catalyst composition and preparation method are relatively simple, the reaction raw materials are cheap and easy to obtain, the reaction conditions are easy to control, the requirements for the reaction device are low, it is easy to carry out large-scale production, and the production cost can be significantly reduced; (2) The perovskite oxide is modified by acid etching to increase its active site density, and then the stability of the catalyst is improved by heat treatment; (3) In the process of selective oxidation of toluene to produce benzoic acid, chlorine will not be introduced, and the high-quality benzoic acid obtained can be widely used in medical and food; (4) Experimental data show that the modified perovskite oxide catalyst is used in the reaction of selective oxidation of toluene to produce benzoic acid, the toluene conversion rate reaches 24.8%, and the selectivity of benzoic acid can reach 82.7%, which has good activity and selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is the XRD spectrum of the perovskite oxide prepared in Example 2;

[0022] Figure 2 The XRD spectra of the catalysts recovered after the perovskite oxides prepared in Examples 4 to 7 are:

[0023] Figure 3 The schematic diagram of the modified LaMnO3 perovskite oxide catalyst prepared by the present invention for the solvent-free selective oxidation of toluene to produce benzoic acid;

[0024] Figure 4 XRD spectra of the catalysts recovered after the perovskite oxides prepared in Examples 8 to 12;

[0025] Figure 5 This is a graph showing the change in toluene conversion rate over time in the solvent-free oxidation of toluene in Example 15;

[0026] Figure 6 This is a curve diagram showing the change in conversion rate of toluene to benzoic acid by solvent-free oxidation as a function of catalyst content in Example 17;

[0027] Figure 7 The XRD spectra of the sixth cycle recovery of perovskite oxide and the fresh catalyst in Example 5;

[0028] Figure 8 The physical adsorption-desorption isotherms of the perovskite oxides prepared in Comparative Example 2, Example 2 and Example 5;

[0029] Fig. 9 is a pore size distribution curve diagram of the perovskite oxides prepared in Comparative Example 2, Example 2 and Example 5;

[0030] Fig.10HRTEM (AB), SAED (C) images and EDS spectrum (D) of La, Mn and O elements of the perovskite oxide catalyst in Example 5. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the embodiments and drawings.

[0032] Example 1: The modified LaMnO3 perovskite oxide catalyst provided in this example is: LaMnO3 perovskite oxide is etched statically with 0.5 mol / L HNO3 solution for 210 min.

[0033] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0034] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0035] (2) Catalyst etching. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 210 min. After the treatment process, the obtained precipitate was repeatedly filtered with a circulating water vacuum pump until the filtrate was neutral. The filter cake was dried overnight and ground to obtain the acid-etched catalyst, which was recorded as LMO-NA-210.

[0036] Application Example 1: The perovskite oxide catalyst prepared in Example 1 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0037] Catalyst LMO-NA-210 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0038] Example 2: The modified LaMnO3 perovskite oxide catalyst provided in this example is: LaMnO3 perovskite oxide is etched statically with 0.5 mol / L HNO3 solution for 230 min.

[0039] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0040] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0041] (2) Catalyst etching. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 230 min. After the treatment process, the obtained precipitate was repeatedly filtered using a circulating water vacuum pump until the filtrate was neutral. The filter cake was dried overnight and ground to obtain the acid-etched catalyst, which was recorded as LMO-NA-230.

[0042] Application Example 2: The perovskite oxide catalyst prepared in Example 2 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0043] Catalyst LMO-NA-230 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0044] Example 3: The modified LaMnO3 perovskite oxide catalyst provided in this example is: LaMnO3 perovskite oxide is etched statically with 0.5 mol / L HNO3 solution for 250 min.

[0045] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0046] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0047] (2) Catalyst etching. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 250 min. After the treatment process, the obtained precipitate is repeatedly filtered with a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst, which is recorded as LMO-NA-250.

[0048] Application Example 3: The perovskite oxide catalyst prepared in Example 3 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0049] Catalyst LMO-NA-250 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0050] The results of the determination of the reaction activity of the catalysts in Application Examples 1 to Application Examples 3 for the solvent-free molecular oxygen oxidation of toluene to produce benzoic acid are shown in Table 1.

[0051] Table 1 Reaction activity of catalytic solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Application Examples 1 to 3

[0052]

[0053] It can be seen from Table 1 that the acid etching time affects the catalytic activity of the catalyst. When the acid etching time is 210min, the conversion rate of toluene is low. It may be that the acid etching time is not enough, and the active sites required for the reaction cannot be provided, resulting in low catalytic activity. With the extension of etching time, the catalytic activity reaches the maximum value at 230min, and the toluene conversion rate is 29.6%, and the main product is benzoic acid. This may be because the acid-etched catalyst has a larger specific surface area and more mesoporous structure, which has a greater chance of contact with the reactants and a good catalytic effect. At the same time, the oxygen vacancy density of the etched catalyst increases significantly, which promotes the activation of toluene and the selective conversion to benzoic acid. When the acid etching time is 250min, the conversion rate of toluene decreases, which may be due to excessive acid etching, loss of surface active sites, and reduced catalyst activity. Therefore, the LaMnO3 perovskite oxide catalyst with an acid etching time of 230min has a better conversion rate of toluene and selectivity of benzoic acid.

[0054] The XRD test of the perovskite oxide prepared in Example 2 was carried out on an X-ray diffractometer. The XRD spectrum is as follows: Figure 1 As shown. After 230 minutes of HNO3 etching, the sample still maintains a perovskite-based structure. The diffraction peak intensity of LMO-NA-230 is somewhat weakened compared to before acid etching. At the same time, weak characteristic diffraction peaks belonging to the orthorhombic phase MnO2 appear at 2θ of 45.1° and 61.7° (JCPDS 44-0142). However, the recovered catalyst cannot maintain the original phase, indicating that the stability of the catalyst is poor. Based on the fact that the recovered catalyst is difficult to maintain the original phase, highlighting its lack of stability, heat treatment is used to improve the stability of the catalyst. This initiative aims to promote favorable changes in the internal structure of the catalyst by regulating specific temperature and time conditions during the heat treatment process, thereby enhancing its ability to maintain its own phase during use and recycling, thereby improving the overall stability performance.

[0055] Example 4: The modified LaMnO3 perovskite oxide catalyst provided in this example is: LaMnO3 perovskite oxide is etched with 0.5 mol / L HNO3 solution for 230 min, and then calcined in a muffle furnace at 400°C for 24 h.

[0056] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0057] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0058] (2) Etching of the catalyst. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 230 min. After the treatment process, the obtained precipitate is repeatedly filtered using a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst.

[0059] (3) Heat treatment of the catalyst: The acid-etched catalyst was calcined in a muffle furnace at 400°C for 24 h and recorded as LMO-NA-230-400-24.

[0060] Application Example 4: The perovskite oxide catalyst prepared in Example 4 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0061] Catalyst LMO-NA-230-400-24 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0062] Example 5: The modified LaMnO3 perovskite oxide catalyst provided in this example is: LaMnO3 perovskite oxide is etched with 0.5 mol / L HNO3 solution for 230 min, and then calcined at 500°C in a muffle furnace for 24 h.

[0063] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0064] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0065] (2) Etching of the catalyst. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 230 min. After the treatment process, the obtained precipitate is repeatedly filtered using a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst.

[0066] (3) Heat treatment of the catalyst: The acid-etched catalyst was calcined in a muffle furnace at 500°C for 24 h and recorded as LMO-NA-230-500-24.

[0067] Application Example 5: The perovskite oxide catalyst prepared in Example 5 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0068] Catalyst LMO-NA-230-500-24 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0069] Example 6: The modified LaMnO3 perovskite oxide catalyst provided in this example is: LaMnO3 perovskite oxide is etched with 0.5 mol / L HNO3 solution for 230 min, and then calcined at 600°C in a muffle furnace for 24 h.

[0070] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0071] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0072] (2) Etching of the catalyst. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 230 min. After the treatment process, the obtained precipitate is repeatedly filtered using a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst.

[0073] (3) Heat treatment of the catalyst: The acid-etched catalyst was calcined in a muffle furnace at 600°C for 24 h and recorded as LMO-NA-230-600-24.

[0074] Application Example 6: The perovskite oxide catalyst prepared in Example 6 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0075] Catalyst LMO-NA-230-600-24 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0076] Example 7: The modified LaMnO3 perovskite oxide catalyst provided in this example is: LaMnO3 perovskite oxide is statically etched with 0.5 mol / L HNO3 solution for 230 min, and then calcined at 700°C in a muffle furnace for 24 h.

[0077] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0078] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0079] (2) Etching of the catalyst. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 230 min. After the treatment process, the obtained precipitate is repeatedly filtered using a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst.

[0080] (3) Heat treatment of the catalyst: The acid-etched catalyst was calcined in a muffle furnace at 700°C for 24 h and recorded as LMO-NA-230-700-24.

[0081] Application Example 7: The perovskite oxide catalyst prepared in Example 7 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0082] Catalyst LMO-NA-230-700-24 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0083] The XRD test of the catalyst recovered after the perovskite oxide reaction obtained in Examples 4 to 7 was carried out on an X-ray diffractometer. The XRD spectrum is as follows: Figure 2 shown.

[0084] The results of the determination of the reaction activity of the catalysts in Application Examples 4 to 7 for the solvent-free molecular oxygen oxidation of toluene to produce benzoic acid are shown in Table 2. After heat treatment of LMO-NA-230 at different temperatures, the LaMnO3 perovskite oxide phase was still maintained. However, the catalyst was recovered after the reaction. Figure 2It can be seen that the recovered catalysts have different degrees of phase transition. Comparing the heat treatment temperature, it was found that after the etched catalyst was calcined at 500°C for 24 hours, the main phase of the recovered catalyst was still LaMnO3 (JCPDS 54-1275), but the characteristic diffraction peaks belonging to Mn2O3 still appeared at 2θ of 38.5°, 45.1°, 49.3°, 55.1°, and 65.8° (JCPDS 41-1442), but it was better than the catalysts calcined at other temperatures. The catalytic activity of LMO-NA-230-500-24 is the highest, with a conversion rate of 24.8% and a benzoic acid selectivity of 82.7%. Its schematic diagram is shown below. Figure 3 Based on the unique properties of the catalyst, Mn 4+ Ions and Mn 3+ The ions undergo a dynamic redox process on their surface, which significantly promotes the solvent-free oxidation of toluene to produce benzoic acid, and helps to improve the conversion rate and selectivity of benzoic acid. It was found that after the etched catalyst was calcined at 400℃ for 24h, the characteristic diffraction peak of MnO2 appeared (JCPDS 30-0820), and the characteristic peak of perovskite LaMnO3 only appeared at 32.4°. As shown in Table 2, the conversion rate of toluene was only 18.3%. With the increase of calcination temperature, after the reaction of the catalyst calcined at 600℃, the LaMnO3 phase basically turned into Mn2O3, and after the reaction of the catalyst calcined at 700℃, the phase was further oxidized to Mn3O4 (JCPDS24-0734), and the conversion rate of toluene was less than 20%.

[0085] Table 2 Reaction activity of catalytic solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Application Examples 4 to 7

[0086]

[0087] Example 8: The modified LaMnO3 perovskite oxide catalyst provided in this example is: LaMnO3 perovskite oxide is etched with 0.5 mol / L HNO3 solution for 230 min, and then calcined in a muffle furnace at 500°C for 1 h.

[0088] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0089] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0090] (2) Etching of the catalyst. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 230 min. After the treatment process, the obtained precipitate is repeatedly filtered using a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst.

[0091] (3) Heat treatment of the catalyst: The acid-etched catalyst was calcined in a muffle furnace at 500°C for 1 h and recorded as LMO-NA-230-500-1.

[0092] Application Example 8: The perovskite oxide catalyst prepared in Example 8 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0093] Catalyst LMO-NA-230-500-1 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0094] Example 9: The modified LaMnO3 perovskite oxide catalyst provided in this example is: LaMnO3 perovskite oxide is etched with 0.5 mol / L HNO3 solution for 230 min, and then calcined in a muffle furnace at 500°C for 3 h.

[0095] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0096] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0097] (2) Etching of the catalyst. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 230 min. After the treatment process, the obtained precipitate is repeatedly filtered using a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst.

[0098] (3) Heat treatment of the catalyst: The acid-etched catalyst was calcined in a muffle furnace at 500°C for 3 h and recorded as LMO-NA-230-500-3.

[0099] Application Example 9: The perovskite oxide catalyst prepared in Example 9 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0100] Catalyst LMO-NA-230-500-3 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0101] Example 10: The modified LaMnO3 perovskite oxide catalyst provided in this example is: LaMnO3 perovskite oxide is etched with 0.5 mol / L HNO3 solution for 230 min, and then calcined in a muffle furnace at 500°C for 6 h.

[0102] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0103] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0104] (2) Etching of the catalyst. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 230 min. After the treatment process, the obtained precipitate is repeatedly filtered using a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst.

[0105] (3) Heat treatment of the catalyst: The acid-etched catalyst was calcined in a muffle furnace at 500°C for 6 h and was recorded as LMO-NA-230-500-6.

[0106] Application Example 10: The perovskite oxide catalyst prepared in Example 10 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0107] Catalyst LMO-NA-230-500-6 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0108] Example 11: The modified LaMnO3 perovskite oxide catalyst provided in this example is: LaMnO3 perovskite oxide is statically etched with 0.5 mol / L HNO3 solution for 230 min, and then calcined in a muffle furnace at 500°C for 12 h.

[0109] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0110] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0111] (2) Etching of the catalyst. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 230 min. After the treatment process, the obtained precipitate is repeatedly filtered using a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst.

[0112] (3) Heat treatment of the catalyst: The acid-etched catalyst was calcined in a muffle furnace at 500°C for 12 h and recorded as LMO-NA-230-500-12.

[0113] Application Example 11: The perovskite oxide catalyst prepared in Example 11 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0114] Catalyst LMO-NA-230-500-12 titanium ore oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0115] Example 12: The modified LaMnO3 perovskite oxide catalyst provided in this example is: LaMnO3 perovskite oxide is etched with 0.5 mol / L HNO3 solution for 230 min, and then calcined at 500°C in a muffle furnace for 48 h.

[0116] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0117] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0118] (2) Etching of the catalyst. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 230 min. After the treatment process, the obtained precipitate is repeatedly filtered using a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst.

[0119] (3) Heat treatment of the catalyst: The acid-etched catalyst was calcined in a muffle furnace at 500°C for 48h and recorded as LMO-NA-230-500-48.

[0120] Application Example 12: The perovskite oxide catalyst prepared in Example 12 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0121] Catalyst LMO-NA-230-500-48 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0122] The XRD test of the catalyst recovered after the reaction of the perovskite oxide obtained in Examples 8 to 12 was carried out on an X-ray diffractometer. The XRD spectrum is as follows: Figure 4 shown.

[0123] The results of the determination of the reaction activity of the catalysts in Application Examples 8 to Application Examples 12 for the solvent-free molecular oxygen oxidation of toluene to produce benzoic acid are shown in Table 3.

[0124] Table 3 shows the effect of heat treatment time on the catalytic performance of LMO-NA-230 catalyst. At a calcination temperature of 500°C, it is found that the conversion rate tends to decrease gradually with the increase of time.

[0125] pass Figure 4It was found that when the calcination time was short, the recovered catalyst could not maintain the perovskite phase, and the catalyst completely turned into the phase of Mn2O3 (JCPDS 41-1442). When the calcination time was 12h, the recovered catalyst had the diffraction peak of LaMnO3 (JCPDS 54-1275). Only after calcination at 500℃ for 24h, although the Mn2O3 phase still existed, the main phase of the recovered catalyst was LaMnO3, the conversion rate of LMO-NA-230-500-24 was 24.8%, and the selectivity of benzoic acid was 82.7%. Continuing to extend the calcination time, it was found that the purity of the catalyst phase after the reaction was not further improved, and the catalytic performance continued to decline. The conversion rate of LMO-NA-230-500-48 was reduced to 20.6%. This may be due to the long heat treatment time, the catalyst sintering, and the reduction of catalytic activity.

[0126] Table 3 Reaction activity of catalytic solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Examples 8 to 12

[0127]

[0128] Application Example 13: The difference from Application Example 5 is: catalytic reaction temperature. In this embodiment, the reaction temperatures are set to 150°C, 160°C, 170°C (i.e., Application Example 5) and 180°C, respectively. The results of the measurement of the reaction activity of catalytic solvent-free molecular oxygen oxidation of toluene to produce benzoic acid are shown in Table 4 below.

[0129] Table 4 Reaction activity of catalytic solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Application Example 13

[0130]

[0131] When the reaction temperature is 150℃, the conversion rate of toluene and the selectivity of benzoic acid are 10.7% and 80.5% respectively. When the reaction temperature is increased to 170℃, the conversion rate of toluene increases to 24.8% and the selectivity of benzoic acid also increases to 82.7%. When the reaction temperature is 180℃, the conversion rate of toluene increases slowly, from 24.8% to 25.7%, and the selectivity of benzoic acid also increases to 83.3%. Therefore, the catalyst has a better performance when the reaction temperature is 170℃.

[0132] Application Example 14: The difference from Application Example 5 is that: the catalytic reaction pressure, the reaction pressure of this embodiment is set to 1MPa, 2MPa, 2.5MPa and 3MPa (i.e., Application Example 5), and the results of the determination of the reaction activity of catalytic toluene solvent-free molecular oxygen oxidation to benzoic acid are shown in Table 5 below. When the oxygen pressure is 1MPa, the conversion rate of toluene is 12.8%, and the selectivity of benzoic acid is 75.6%. When the oxygen pressure is increased to 2MPa, the conversion rate of toluene is significantly increased to 19.4%. When the pressure is further increased to 2.5MPa, the conversion rate of toluene continues to increase to 22.9%, and when the pressure is increased to 3MPa, the conversion rate reaches 24.8%, and the selectivity of benzoic acid is increased to 82.7%. As the pressure gradually increases, the growth rate of the conversion rate continues to decrease and eventually tends to be flat. It can be seen from this that when the oxygen pressure is low, oxygen dissolves less in the solution and is less adsorbed by the catalyst, resulting in relatively less contact between oxygen and substrate molecule toluene, and low reaction activity. When the oxygen pressure is increased, the amount of oxygen adsorbed and activated by the catalyst in the reaction increases accordingly, which is beneficial to weaken the effect of oxygen molecule diffusion on toluene oxidation and improve the reaction activity of toluene.

[0133] Table 5 Reaction activity of catalytic solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Application Example 14

[0134]

[0135] Application Example 15: The difference from Application Example 5 is: catalytic reaction time. In this embodiment, the reaction time is set to 1h, 3h, 6h, 12h, 18h, 24h (i.e., Application Example 5), 30h, and 48h, respectively. The measurement results of the reaction activity of catalytic solvent-free molecular oxygen oxidation of toluene to produce benzoic acid are shown in Table 6 below.

[0136] When the reaction time is 1h, toluene has almost no reaction activity. As time goes by, the conversion rate of toluene and the selectivity of benzoic acid are further improved. Figure 5 It can be found that the time curve of toluene solvent-free oxidation is an S-shaped curve. When the reaction time is 24h, the conversion rate of toluene is increased to 24.8%, and the selectivity of benzoic acid is also increased to 82.7%. The conversion rate of toluene and the selectivity of benzoic acid are not further improved by continuing to extend the reaction time, which may be due to the gradual decrease in the concentration of toluene as the reaction proceeds. When the concentration of toluene is reduced to a certain extent, the reaction rate will be limited. Even if the reaction time is extended, it is difficult to significantly improve the conversion rate due to the insufficient amount of reactants.

[0137] Table 6 Reaction activity of catalytic solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Application Example 15

[0138]

[0139] Application Example 16: The difference from Application Example 5 is: the rotation speed. In this embodiment, the rotation speed is set to 200 rpm, 400 rpm, 600 rpm, 800 rpm, 1000 rpm (i.e., Application Example 5) and 1200 rpm respectively. The measurement results of the reaction activity of catalyzing the solvent-free molecular oxygen oxidation of toluene to produce benzoic acid are shown in Table 7 below.

[0140] Table 7 Reaction activity of catalytic solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Application Example 16

[0141]

[0142] When the speed is in the range of 200-1000rpm, the conversion rate of toluene increases with the increase of speed, and the conversion rate increases from 11.5% to 24.8%, while it changes little in the range of 1000-1200rpm. This shows that in the speed range of 1000-1200rpm, the influence of external diffusion can be eliminated in the early stage of the reaction, and toluene oxidation is controlled by chemical reaction. Increasing the speed can enhance the mixing effect of the reaction system, allowing oxygen and toluene molecules to contact more fully, thereby increasing the reaction rate.

[0143] Application Example 17: The difference from Application Example 5 is: the amount of catalyst. In this embodiment, the amount of catalyst is set to 0.1g, 0.15g, 0.2g (i.e., Application Example 5) and 0.25g respectively. The measurement results of the reaction activity of catalyzing the solvent-free molecular oxygen oxidation of toluene to produce benzoic acid are shown in Table 8 below.

[0144] Table 8 Reaction activity of catalytic solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Application Example 17

[0145]

[0146] When the mass of the catalyst LMO-NA-230-500-24 is 0.1g, the conversion rate of toluene is 9.78%, and the selectivity of benzoic acid is 77.4%. As the mass of the catalyst gradually increases, the conversion rate of toluene shows an upward trend, and the conversion rates of toluene are 15.1%, 24.8% and 25.9%, respectively. It can be found that when the mass of toluene increases to 0.25g, the conversion rate of toluene is not further improved. This shows that the catalytic reaction activity of LMO-NA-230-500-24 is related to the amount of catalyst. If the amount of catalyst is too low, it may be because it provides fewer active sites and cannot meet the number of active sites required for the reaction. Too much catalyst may have excessive adsorption on toluene, thereby reducing the activity of the reaction. Figure 6 It can be found that the catalyst dosage has a linear relationship with the initial conversion, which indicates that the initial oxidation rate is controlled by chemical reaction rather than diffusion mass transfer.

[0147] Application Example 18: The activity stability experiment of the catalyst was carried out at a reaction temperature of 170° C., a reaction pressure of 3 MPa, a reaction time of 24 h, and a rotation speed of 1000 rpm.

[0148] The perovskite oxide catalyst recovered after reacting for 24 hours in Application Example 5 was washed with anhydrous ethanol, filtered through a No. 4 sand core funnel 5 times, and after washing away the reaction liquid, it was dried in an oven at 80° C. for 12 hours to obtain a recovered catalyst LMO-NA-230-500-24-R1.

[0149] The catalyst (0.2 g) of Example LMO-NA-230-500-24-R1 and toluene (10 mL) were added to a kettle reactor and reacted under the conditions of a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0150] Application Example 19: The perovskite oxide catalyst recovered after the catalyst LMO-NA-230-500-24-R1 in Application Example 18 was reacted for 24 hours was washed with anhydrous ethanol, filtered through a No. 4 sand core funnel 5 times, and after washing away the reaction liquid, it was dried in an oven at 80°C for 12 hours to obtain LMO-NA-230-500-24-R2.

[0151] LMO-NA-230-500-24-R2 catalyst (0.2 g) and toluene (10 mL) were added to a kettle reactor and reacted under the conditions of a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0152] Application Example 20: The perovskite oxide catalyst recovered after the catalyst LMO-NA-230-500-24-R2 in Application Example 19 was reacted for 24 hours was washed with anhydrous ethanol, filtered through a No. 4 sand core funnel 5 times, and after washing away the reaction liquid, it was dried in an oven at 80°C for 12 hours to obtain LMO-NA-230-500-24-R3.

[0153] Catalyst LMO-NA-230-500-24-R3 (0.2 g) and toluene (10 mL) were added to a kettle reactor and reacted under the conditions of a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0154] Application Example 21: The perovskite oxide catalyst recovered after the catalyst LMO-NA-230-500-24-R3 in Application Example 20 was reacted for 24 hours was washed with anhydrous ethanol, filtered through a No. 4 sand core funnel 5 times, and after washing away the reaction liquid, it was dried in an oven at 80°C for 12 hours to obtain LMO-NA-230-500-24-R4.

[0155] LMO-NA-230-500-24-R4 catalyst (0.2 g) and toluene (10 mL) were added to a kettle reactor and reacted under the conditions of a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0156] Application Example 22: The perovskite oxide catalyst recovered after the catalyst LMO-NA-230-500-24-R4 in Application Example 21 was reacted for 24 hours was washed with anhydrous ethanol, filtered through a No. 4 sand core funnel 5 times, and after washing away the reaction liquid, it was dried in an oven at 80°C for 12 hours to obtain LMO-NA-230-500-24-R5.

[0157] LMO-NA-230-500-24-R5 catalyst (0.2 g) and toluene (10 mL) were added to a kettle reactor and reacted under the conditions of a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0158] The results of the determination of the reaction activity of catalyzing the solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Application Example 5 and Application Example 18 to Application Example 22 are shown in Table 9 below.

[0159] It can be seen from Table 9 that the catalytic activity and selectivity for the target product benzoic acid of the perovskite oxide in the solvent-free molecular oxygen oxidation of toluene to produce benzoic acid remained relatively stable after 6 cycles of evaluation, with a toluene conversion rate (24.8%) and a benzoic acid selectivity (82.7%).

[0160] Figure 7 The XRD spectra of the sixth cycle recycled and fresh catalyst are shown in Figure 2. Figure 7 It can be seen that although a small number of characteristic diffraction peaks of Mn2O3 appear, the main phase of LMO-NA-230-500-24-R5 is LaMnO3. This shows that after the catalyst heat-treated at 500℃ was evaluated for catalytic performance six times, the crystal structure of the catalyst remained relatively stable, and it had good activity stability and recyclability.

[0161] Table 9 Reaction activity of catalytic solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Application Example 5, Application Example 18-Application Example 22

[0162]

[0163] Comparative Application Example 1: Toluene (10 mL) was added to a kettle reactor, and the reaction was carried out under the following conditions: a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0164] Comparative Example 2: The catalyst provided in this comparative example is LaMnO3 perovskite oxide.

[0165] The preparation method of the above-mentioned perovskite oxide catalyst includes the following steps: synthesizing LaMnO3 catalyst by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) are dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Then, citric acid is added as a chelating agent with a molar ratio of 1:1 to the total metal ions, and stirring is continued until it is completely dissolved. The mixed solution is stirred in an oil bath at 80°C for more than 5 hours until the solution gradually becomes viscous and finally forms a stable viscous gel. The obtained gel is placed in an oven and dried at 100°C for 12 hours. The dried gel is ground into powder, calcined at 400°C in a muffle furnace for 2 hours, then heated to 750°C and continued to calcine for 4 hours, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0166] Application Comparative Example 2: The perovskite oxide catalyst prepared in Comparative Example 2 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0167] Catalyst LaMnO3 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170°C, a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0168] Comparative Example 3: The perovskite oxide catalyst provided in this comparative example is to etch LaMnO3 perovskite oxide with 0.5 mol / L HNO3 solution for 200 min.

[0169] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0170] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0171] (2) Catalyst etching. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 200 min. After the treatment process, the obtained precipitate was repeatedly filtered with a circulating water vacuum pump until the filtrate was neutral. The filter cake was dried overnight and ground to obtain the acid-etched catalyst, which was recorded as LMO-NA-200.

[0172] Application Comparative Example 3: The perovskite oxide catalyst prepared in Comparative Example 3 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0173] Catalyst LMO-NA-200 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0174] Comparative Example 4: The perovskite oxide catalyst provided in this comparative example is: LaMnO3 perovskite oxide is etched statically with 0.5 mol / L HNO3 solution for 280 min.

[0175] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0176] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h to remove excess water. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0177] (2) Catalyst etching. First, prepare a 0.5 mol / L HNO3 solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of HNO3 solution, and let it stand at room temperature for 280 min. After the treatment process, the obtained precipitate is repeatedly filtered with a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst, which is recorded as LMO-NA-280.

[0178] Application Comparative Example 4: The perovskite oxide catalyst prepared in Comparative Example 4 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0179] Catalyst LMO-NA-280 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0180] The results of the determination of the reaction activity of catalyzing the solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Application Comparative Examples 1 to Application Comparative Examples 4 are shown in Table 10.

[0181] Table 10 Reaction activity of catalytic solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Application Example 5, Application Comparative Example 1 to Application Comparative Example 4

[0182]

[0183] As shown in Table 10, from Application Comparative Example 1 and Application Example 5, it can be seen that in the absence of a catalyst during the reaction process, there is only a 4.09% conversion rate, the main product is benzoic acid, and the selectivity is relatively high. This shows that toluene can still undergo self-oxidation without a catalyst, but has a higher reaction activation energy and low reaction activity. From Application Comparative Example 2 and Application Example 2, it can be seen that when LaMnO3 catalyst is used, the toluene conversion rate and benzoic acid selectivity reach 15.1% and 80.4% respectively, indicating that LaMnO3 is an active catalyst for liquid phase oxidation of toluene, but the conversion rate is lower than that of the catalyst after acid etching. Figure 8 It can be seen that according to the IUPAC classification, all samples show similar type IV isotherms and H3 type hysteresis loops at relative pressure. The LaMnO3 catalyst shows weaker adsorption and hysteresis loops, which may be due to the presence of a small number of stacking pores. As shown in Table 11, etching increases the specific surface area of ​​the catalyst from 13.3 m 2 / g increased to 140m 2 / g, and the pore volume increased nearly tenfold. Although the pore size value did not change much before and after etching, the pore volume increased significantly ( Fig. 9 ). The reason for the significant increase in specific surface area may be that after part of the La element is etched, the catalyst forms more mesoporous structures. The increase in specific surface area is not only conducive to the entry of toluene into the interior of the catalyst, but also increases the contact area between the catalyst and toluene, thereby improving the catalytic activity of toluene oxidation. The increased specific surface area and pore structure improve the catalytic activity by providing more active sites. It can be seen from Application Comparative Example 3 and Application Example 5 that in the reaction process of toluene solvent-free molecular oxygen oxidation to produce benzoic acid, when the acid etching time is short, the conversion rate of toluene is not significantly improved. However, it can be seen from Application Comparative Example 3 and Application Example 5 that when the acid etching time is extended to 280min, the toluene conversion rate of LMO-NA-280 is only 10.6%, which is even lower than the catalytic performance of unetched LaMnO3. This may be due to excessive acid etching and loss of surface active sites, resulting in reduced catalyst activity.

[0184] Table 11 Grain size, elemental composition and texture properties of catalysts LMO, LMO-NA-230 and LMO-NA-230-500-24

[0185]

[0186] In the table: a Using the Scherrer equation, b Determined by ICP-OES, c Determined by BET method, d The pore volume and average pore size were determined by the BJH method.

[0187] The elemental composition of LaMnO3, LMO-NA-230 and LMO-NA-230-500-24 samples was analyzed by ICP-OES, and the results are shown in Table 11. Etching reduced the molar ratio of La to Mn in the catalyst from 0.98 (LaMnO3) to 0.35 (LMO-NA-230), indicating that the La ions in LaMnO3 were selectively etched in situ. The La / Mn ratio of the calcined catalyst (LMO-NA-230-NA-230) was 0.32, which was not significantly changed compared with that before calcination. The grain size of the catalyst was calculated using the Scherrer formula, and the results are shown in Table 11. The grain size of LaMnO3 was 40.5nm, and the grain size of the etched catalyst LMO-NA-230 was 20.4nm, indicating that the dilute nitric acid solution had a selective dissolution effect on La in LaMnO3, and the grain size became smaller and the specific surface area increased. This can provide more possible active sites for the catalytic reaction. The phase of the etched catalyst did not change significantly after heat treatment, and its grain size increased slightly. XRD The diameter of the crystal increases from 20.4 nm before heat treatment to 24.2 nm. This may be because during the calcination process, metal ions and oxygen ions can move in the crystal lattice, causing adjacent small grains to merge into large grains, resulting in grain growth.

[0188] Fig.10 This is a high-resolution transmission electron microscopy image of LMO-NA-230-500-24. Fig.10 As can be seen from (A) in the figure, the catalyst exhibits a uniform irregular particle distribution and a porous microstructure. Fig.10 In (B), it can be observed that there is an obvious lattice structure on the surface of LMO-NA-230-500-24, which is consistent with the XRD results. The lattice spacing of the sample after etching and heat treatment is mainly 0.256nm and 0.286nm, corresponding to the (204) and (212) crystal planes of LaMnO3, respectively. Fig.10 In (B), disordered and blurred lattice fringes can also be observed, which may be attributed to the location of defects. These defects are related to oxygen vacancies, which play an important role in the catalytic oxidation of toluene. The polycrystalline nature of the catalyst is revealed by the corresponding selected area electron diffraction (SAED) pattern, which is consistent with the XRD spectrum of the catalyst. In addition, the EDS element mapping of LMO-NA-230-500-24 shows that the La, Mn and O components in the sample are in a consistent and highly dispersed state, indicating that the pure phase structure of the LMO-NA-230-500-24 catalyst is consistent.

[0189] Comparative Example 5: The perovskite oxide catalyst provided in this comparative example is: LaMnO3 perovskite oxide is etched with 0.5 mol / L acetic acid solution for 300 min, and then calcined at 500° C. in a muffle furnace for 24 h.

[0190] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0191] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0192] (2) Etching of the catalyst. First, prepare a 0.5 mol / L acetic acid solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of acetic acid solution, and let it stand at room temperature for 300 min. After the treatment process is completed, the obtained precipitate is repeatedly filtered using a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst.

[0193] (3) Heat treatment of the catalyst: The acid-etched catalyst was calcined in a muffle furnace at 500°C for 24 h and recorded as LMO-HOAc-300-500-24.

[0194] Application Comparative Example 5: The perovskite oxide catalyst prepared in Comparative Example 5 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0195] Catalyst LMO-HOAc-300-500-24 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0196] Comparative Example 6: The perovskite oxide catalyst provided in this comparative example is: LaMnO3 perovskite oxide is etched with 0.5 mol / L sulfuric acid solution for 230 min, and then calcined at 500° C. in a muffle furnace for 24 h.

[0197] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0198] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0199] (2) Etching of the catalyst. First, prepare a 0.5 mol / L sulfuric acid solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of sulfuric acid solution, and let it stand at room temperature for 230 min. After the treatment process is completed, the obtained precipitate is repeatedly filtered using a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst.

[0200] (3) Heat treatment of the catalyst: The acid-etched catalyst was calcined in a muffle furnace at 500°C for 24 h and recorded as LMO-SA-230-500-24.

[0201] Application Comparative Example 6: The perovskite oxide catalyst prepared in Comparative Example 6 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0202] Catalyst LMO-SA-230-500-24 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0203] Comparative Example 7: The perovskite oxide catalyst provided in this comparative example is: LaMnO3 perovskite oxide is statically etched with 0.5 mol / L phosphoric acid solution for 260 min, and then calcined at 500° C. in a muffle furnace for 24 h.

[0204] The method for preparing the above-mentioned perovskite oxide catalyst comprises the following steps:

[0205] (1) LaMnO3 catalyst was synthesized by sol-gel method. First, La(NO3)2·6H2O (0.015 mol) and Mn(NO3)2·4H2O (0.015 mol) were dissolved in ionized water (100 mL) and stirred to obtain a mixed solution. Citric acid was then added as a chelating agent at a molar ratio of 1:1 to the total metal ions, and stirring was continued until it was completely dissolved. The mixed solution was stirred in an oil bath at 80°C for more than 5 h until the solution gradually became viscous and finally formed a stable viscous gel. The obtained gel was placed in an oven and dried at 100°C for 12 h. The dried gel was ground into powder, calcined in a muffle furnace at 400°C for 2 h, then heated to 750°C and continued to calcine for 4 h, and naturally cooled to room temperature to obtain a LaMnO3 sample.

[0206] (2) Etching of the catalyst. First, prepare a 0.5 mol / L phosphoric acid solution. Then, weigh 1 g of LaMnO3 powder and put it into 100 mL of phosphoric acid solution, and let it stand at room temperature for 260 min. After the treatment process is completed, the obtained precipitate is repeatedly filtered using a circulating water vacuum pump until the filtrate is neutral. The filter cake is dried overnight and ground to obtain the acid-etched catalyst.

[0207] (3) Heat treatment of the catalyst: The acid-etched catalyst was calcined in a muffle furnace at 500°C for 24 h and was recorded as LMO-PA-260-500-24.

[0208] Application of Comparative Example 7: The perovskite oxide catalyst prepared in Comparative Example 7 is used as a catalyst in the solvent-free selective oxidation of toluene to produce benzoic acid, and the method is as follows:

[0209] Catalyst LMO-PA-260-500-24 perovskite oxide (0.2 g) and toluene (10 mL) were added to a kettle reactor with a stirring speed of 1000 rpm, a reaction temperature of 170° C., a reaction pressure of 3 MPa, and a reaction time of 24 h.

[0210] The results of the determination of the reaction activity of catalyzing the solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Application Comparative Example 5-Application Comparative Example 7 are shown in Table 12. As can be seen from Table 12, according to Application Comparative Example 5, LaMnO3 is etched in a 0.5mol / L acetic acid solution for 300min, followed by calcination at 500℃ for 24h, which is the best condition for acetic acid etching of LaMnO3. Under this condition, the toluene conversion rate is 20.1% and the selectivity of benzoic acid is 77.1%. According to Application Comparative Example 6, LaMnO3 is etched in a 0.5mol / L sulfuric acid solution for 230min, followed by calcination at 500℃ for 24h, which is the best condition for sulfuric acid etching of LaMnO3. At this time, the toluene conversion rate is 18.3% and the selectivity of benzoic acid is 77.3%. From the comparative application example 7, it can be seen that etching LaMnO3 in a 0.5 mol / L phosphoric acid solution for 260 min and then calcining at 500°C for 24 h is the best condition for etching LaMnO3 with phosphoric acid. In this case, the toluene conversion rate is 16.4% and the selectivity of benzoic acid is 76.1%. Compared with the application example 5, the effects of etching LaMnO3 with acetic acid, sulfuric acid and phosphoric acid are not as good as nitric acid.

[0211] Table 12 Reaction activity of catalytic solvent-free molecular oxygen oxidation of toluene to produce benzoic acid in Application Example 5, Application Comparative Example 5-Application Comparative Example 7

[0212]

Claims

1. A method for preparing a modified LaMnO3 perovskite oxide catalyst, characterized in that: The following steps are involved: (1) Preparation of LaMnO3 perovskite oxide; (2) The LaMnO3 perovskite oxide is subjected to acid etching and heat treatment to obtain a modified LaMnO3 perovskite oxide catalyst.

2. The preparation method according to claim 1, characterized in that: In step (1), LaMnO3 perovskite oxide is prepared by a sol-gel method, the steps are: (11) dissolving La(NO3)2·6H2O and Mn(NO3)2·4H2O in a solvent, stirring, adding citric acid as a chelating agent, and continuing to stir until completely dissolved to obtain a mixed solution; (12) heating and stirring the mixed solution until the solution gradually becomes viscous and eventually forms a stable viscous gel; (13) The viscous gel is dried, ground, and calcined to obtain LaMnO3 perovskite oxide.

3. The preparation method according to claim 2, characterized in that: In step (11), the molar ratio of La(NO3)2·6H2O to Mn(NO3)2·4H2O is 1:1-1.1, and the molar ratio of citric acid to total metal ions is 1:1-1.1; in step (12), the process parameters of heating and stirring are: stirring in an oil bath at 80-85°C for more than 5 hours; in step (13), the process parameters of calcination are: calcining at 400-450°C for 2-2.5 hours, heating to 750-780°C and continuing calcining for 4-6 hours, and then naturally cooling to room temperature.

4. The preparation method according to claim 1, characterized in that: In step (2), the process parameters of the acid etching treatment are: etching with a dilute nitric acid solution with a molar concentration of 0.5-1.0 mol / L for 200-280 min.

5. The preparation method according to claim 1, characterized in that: In step (2), the process parameters of the heat treatment are: heat treatment at 300-700°C for 1-48h.

6. A modified LaMnO3 perovskite oxide catalyst prepared by the preparation method according to any one of claims 1 to 5.

7. The modified LaMnO3 perovskite oxide catalyst according to claim 6, characterized in that: The catalyst has a crystal size of 20-30 nm and a specific surface area of ​​60-70 m 2 / g, pore volume is 0.4-0.5cm 3 / g, average pore size 30-40nm.

8. Use of the modified LaMnO3 perovskite oxide catalyst according to claim 6 in the selective oxidation of toluene to produce benzoic acid.

9. The use according to claim 8, characterized in that: The application method is: using modified LaMnO3 perovskite oxide as a catalyst and oxygen as an oxidant to oxidize toluene under solvent-free conditions to prepare benzoic acid.

10. The use according to claim 9, characterized in that: The ratio of the modified LaMnO3 perovskite oxide catalyst to toluene is 0.10-0.25 g:10 mL, and the oxidation conditions are as follows: reaction temperature is 150-180° C., reaction time is 1-48 h, oxygen pressure is 1-3 MPa, and stirring speed is 200-1200 r / min.

Citation Information

Patent Citations

  • Modified perovskite type catalyst and preparation method thereof

    CN110026185A

Cited By

  • Gd-doped coupling acid etching modified lanthanum-manganese perovskite and preparation method and application thereof

    CN121372396A

  • A gadolinium-doped lanthanum manganese perovskite modified by coupling acid etching, a preparation method and applications thereof

    CN121372396B